Facial expressions of pain in daily clinical practice to assess postoperative pain in children: Reliability and validity of the facial action summary score. (26th January 2021) - Bringuier, Sophie; Macioce, Valerie; Boulhais, Myriam; Dadure, Christophe; Capdevila, Xavier
Abstract: Background: Behavioural pain scales are recommended to assess postoperative pain for children who are too young to use self‐report tools. Their main limitation is underestimation of pain in the days following an intervention. Although relevant, facial expression is not used in daily clinical practice. This prospective study aimed to assess the validity and reliability of the Facial Action Summary Score (FASS), a five‐item scale, to assess postoperative pain until hospital discharge in children <7 years. Methods: Assessments of pain and anxiety of 123 children using FASS and validated scales were used to study the psychometric validity of the FASS in clinical practice. Results: The content validity was previously investigated in a development study. The internal validity of the FASS was high with excellent reliability (intraclass coefficient = 0.94) and a high Cronbach α (0.89). Convergent validity with pain scales (FLACC [Face, Legs, Activity, Cry, Consoling] and FPS‐R [Faces Pain Scale – Revised]) was high ( r  > 0.8). Sensitivity to change was verified by a significant decrease in the score after rescue analgesia. For a threshold of 2/5, the FASS shows excellent specificity (97%) and sensitivity (82%). The low number of false negatives is the main strength of this tool. Conclusions: This work highlights the interest in using facial expression in daily clinical practice to manage postoperative pain. The FASS is easy to use with excellent psychometric properties and is particularly sensitive to measure pain in the days following surgery. Significance: The aim of this study was to prove that facial expression of pain can be used in clinical practice to measure postoperative pain in children. The reduced number of false negatives is the main strength of this tool.